The Good, the Bad and the Lazy teacher: A grounded theory approach to higher education learning situations in Vietnam - Fahmy, Sandra Safwat Youssef (Proceedings of the International Conference on Networked Learning, 2014)
This research discusses the issue of export of education from western countries to developing countries, as Vietnam, using blended learning methodology and the problem of students’ resistance to using the e-learning component of these programs. In this study, the researcher used ethnographic tools for collecting empirical data and constructivist grounded theory tools for coding and analysis of the data. Inspired by Adele Clarke’s writings about Situational Analysis, the researcher developed a "Learning Situation" model with the objective of relating the empirical data to the main research question of the project. This paper details the findings from one focus group conducted in Vietnam followed by line-by-line coding of the data (using Atlas.ti software). The paper focuses on the detailed presentation of two main categories which had the highest occurrence during the analysis of the transcribed focus group. The first category is students’ assumptions that their learning is the responsibility of the teacher and the second is students’ view of the teacher as the centre of all learning processes. Their description of the perfect teacher matches, to a great extent, the picture of a mentor or guru in some Asian religions as Buddhism and Confucianism. The role of the guru or mentor is believed to be to motivate mentees (students) and guide them to reach a better enlightened self. Vietnamese students categorize teachers into "good" and "lazy" teachers, which is a concept that is deeply rooted in Buddhism where learning is viewed as an active process requiring a lot of effort, discipline and dedication. These research findings have many implications for educational institutes that export their educational programs which may have an e-learning component to Vietnam. They should be aware of Vietnamese students’ need for sufficient one-on-one time spent with the teacher, so if the teacher can’t be present physically in class, then this should be substituted by regular scheduled online video meetings with each individual student. Similarly, teachers who teach international programs to Vietnamese students should be aware of their expectations of teachers and thus adopt a role that is less of a facilitator, which is the recently acknowledged and accepted role worldwide, and more of a mentor/guru who has all the answers and provide students with step-by-step guides for learning.